Female inmates learn about education options - Ibrahim, Adnan (New Straits Times, 2012)
KLUANG : Ten female inmates of the Kluang prison were recently given an introduction to education programme offered by Universiti Utara Malaysia's (UUM) Centre of Professional and Continuing Education.